2016
DOI: 10.1038/srep38553
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β controls NF-kappaB activity via IKKγ/NEMO

Abstract: The NF-κB signaling pathway is central for the innate immune response and its deregulation is found in multiple disorders such as autoimmune, chronic inflammatory and metabolic diseases. IKKγ/NEMO is essential for NF-κB activation and NEMO dysfunction in humans has been linked to so-called progeria syndromes, which are characterized by advanced ageing due to age-dependent inflammatory diseases. It has been suggested that glycogen synthase kinase-3β (GSK-3β) participates in NF-κB regulation but the exact mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 54 publications
6
50
0
Order By: Relevance
“…A study describing phosphorylation of Ser43 in NEMO by IKKβ lacks a functional explanation regarding the importance of Ser43 in NEMO for NF-kB activation [31]. Previously, we identified GSK-3β as a kinase that phosphorylates Ser8, 17, and 31 of NEMO during TNFα-induced NF-κB activation [23]. In this study, Ser43 was also found to be phosphorylated.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…A study describing phosphorylation of Ser43 in NEMO by IKKβ lacks a functional explanation regarding the importance of Ser43 in NEMO for NF-kB activation [31]. Previously, we identified GSK-3β as a kinase that phosphorylates Ser8, 17, and 31 of NEMO during TNFα-induced NF-κB activation [23]. In this study, Ser43 was also found to be phosphorylated.…”
Section: Discussionsupporting
confidence: 46%
“…Fixation and staining of the cells for stimulated emission depletion (STED) microscopy have been described previously [23]. Incubation with the primary antibody was performed overnight at 4 °C.…”
Section: Staining Of Cell Cultures For Sted Microscopymentioning
confidence: 99%
“…Moreover, binding and phosphorylation (especially at Ser8, 17, and 31) of NF-κB essential modifier (NEMO, aka IKKγ) by GSK3β is required for its stabilization and the proper mediation of NF-κB signaling. Artificial destabilization of NEMO by replacing the relevant GSK3 target residues by alanine is accompanied by increased Lys63-polyubiquitination of the remaining NEMO molecules, enhanced IKKα and β binding, and elevated constitutive IκBα degradation, effects that could be further intensified by GSK3 inhibition [240].…”
Section: Nf-κb-associated Signalingmentioning
confidence: 99%
“…The subsequent re-activation of the downstream mediator of IRS-1, Akt, has been shown to confer organ protection in many pre-clinical models associated with inflammation including sepsis (33)(34), hemorrhagic shock-induced organ dysfunction (35)(36), and diabetes (20) (37). Indeed re-activating GSK-3b is associated with increased conversion of glucose to glycogen, which could also be a factor contributing to the observed glucose lowering effects in vivo, and is a key regulator of NF-kB activation (38) (39). In the present study we demonstrate inhibition of BTK with ibrutinib protects against the development of insulin resistance by restoring insulin signalling, most likely due to reduced inflammation, in myeloid cells.…”
Section: Discussionmentioning
confidence: 99%